Association of Burkholderia glumae and B. gladioli with panicle blight symptoms on rice in Panama - Nandakumar, R; Rush, MC; Correa Victoria, Fernando J. (Scientific Societies, 2007)
Panicle blight of rice, caused by Burkholderia glumae, has been a serious problem on rice in Japan since 1955. It has been reported from other rice-producing countries around the world and recently was reported on rice in the southern United States (2). A rice producer in Panama contacted us to verify the occurrence of bacterial panicle blight in rice fields where heavy losses were associated with a disease of unknown etiology, but with typical bacterial panicle blight symptoms (2). The observed grain discoloration, sterility, and abortion were thought to be due to the spinki mite, Steneotarsonemus spinki Smiley. After obtaining a USDA-APHIS import permit (73325), rice panicle samples from seven fields in Panama were sent to our laboratory in 2006. Bacteria were isolated from grains showing typical panicle blight symptoms on the semiselective S-Pg medium. Nonfluorescing colonies producing toxoflavin on King's B medium were selected for further identification. Initial PCR analyses, made with DNA isolated directly from grain crushed in sterile water, with B. glumae specific primers (BGF 5?ACACGG AACACCTGGGTA3? and BGR 5?TCGCTCTCCCGAAGAGAT3?) gave a positive reaction for B. glumae in all seven samples. Biolog tests (Biolog Inc, Hayward, CA), fatty acid analysis, and PCR using species-specific primers for B. glumae and B. gladioli (BLF 5?CGAGCT AATACCGCGAAA3? and BLR 5?AGACTCGA GTCAACTGA3?) identified 19 B. glumae and 6 B. gladioli strains among 35 bacterial strains isolated. Only the Biolog and fatty acid analyses identified B. gladioli strains. PCR analysis did not identify B. gladioli strains. To confirm B. gladioli, PCR amplification of the 16S rDNA gene from eight representative strains (four each for B. glumae and B. gladioli) using universal primers (16SF 5?AGAGTTTGATCCTGGCTCAG3? and 16SR5?GGCTACCTTGTTACGACTT3?) and further sequencing of the PCR product was performed. A BLAST analysis of 16S rDNA sequences in the Genbank data base showed 99% sequence similarity for these two species with other published sequences. Our APHIS import permit did not allow us to perform pathogenicity tests with the strains isolated from Panama, but the B. glumae and B. gladioli strains obtained corresponded closely with pathogenic control cultures isolated from rice grown in the United States or with strains obtained from the ATCC. Other B. glumae strains recently isolated from rice in Panama, and identified by PCR, were tested for pathogenicity in tests conducted at CIAT in Colombia and were found to be pathogenic and highly virulent. These strains caused disease on seedlings when inoculated and typical bacterial panicle blight symptoms on panicles when spray inoculated. This disease has caused severe losses in Panama's rice crop for at least 3 years. Similar symptoms reported in Cuba, Haiti, and the Dominican Republic were attributed to damage from the spinki mite in association with Sarocladium oryzae (Sawada) W. Gams & D. Hawksw. (1). Zeigler and Alvarez (3) reported the occurrence of B. glumae in Columbia in 1987, but not in other Latin American countries. Pseudomonas fuscovaginae was reported in association with rice grain discoloration in Panama (4), but to our knowledge, this is the first report of these two Burkholderia species being associated with panicle blight symptoms on rice in Panama.